Incentive-Compatible and Efficient Resource Allocation in Large Economies: An Exact and Local Approach - Harris Dellas; Klaus Nehring (University of California, Department of Economics, 1998)
The main result of this paper characterizes possibly non-symmetric strategy-proof and efficienct choice functions as Perfectly Competitive. Efficiency is defined as impossibility of improvement by reallocation of commodity among finite sets of agents, and largeness of the economy is captured by a weak aggregation-condition called ""local separability."" Individual rationality constraints with respect to an assignment of endowments imply that the resulting allocations must be Walrasian relative to the assignment of endowments. The exact, local approach combined with a normality assumption on the domain of preferences allows the proofs to remain elementary throughout.
Keywords: 330